RETRACTED: Long Noncoding RNA SNHG1 Activates Autophagy and Promotes Cell Invasion in Bladder Cancer - Guo, Changcheng; Li, Xin; Xie, Jinbo; Liu, Dan; Geng, Jiang; Ye, Lin; Yan, Yang; Yao, Xudong; Luo, Ming (Frontiers in Oncology, 2021)
LncRNAs play important roles in bladder cancer. However, only a few studies report on the correlation between lncRNAs expression and autophagy in bladder cancer. This study aimed to explore the effect of lncRNA on autophagy in bladder cancer. The findings showed high expression of SNHG1 in the bladder cancer cells and tumor tissues. The high expression of SNHG1 was positively correlated with bladder cancer cell invasion, proliferation, and autophagy. This finding implies that SNHG1 promotes bladder cancer cell invasion and proliferation via autophagy. Further analysis of the mechanism of action of SNHG1 showed that it functions as a sponge of miRNA-493 in bladder cancer. miRNA-493 binds on the 3’ -UTR of ATG14 mRNA thus affecting ATG14 protein expression, which is implicated in autophagy. These findings are supported by previous preclinical studies using multiple Bca cell lines and TCGA, which demonstrate that SNHG1 plays an oncogenic role by acting as a sponge of miR-493-5p or as its ceRNA. Upregulation of SNHG1 promotes proliferation, invasion, and autophagy of bladder cancer cells through the miR-493-5p/ATG14/autophagy pathway. Therefore, SNHG1 may act as a potential therapeutic target for the treatment of bladder cancer.